PENGARUH RASIO SUMBER LEMAK YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN KELABAU (Osteochilus melanopleurus) - Armain, Nana Nurcahya; Susanto, Adi; Nikhlani, Andi (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
Kelabau fish is a type of freshwater fish that grows slowly even though it is fed adequate nutrition. The research was conducted to analyze the survival, total length growth, weight growth, and specific growth rate of kelabau fish fed with different ratios of lipid sources. This study used a completely randomized design (CRD) with five treatments and three replications. The treatments were A (100% fish oil and 0% corn oil), B (75% fish oil and 25% corn oil), C (50% fish oil and 50% corn oil), D (25% fish oil and 75% corn oil), and E (0% fish oil and 100% corn oil). 20 kelabau fish 40 L-1 volume container were reared for 45 days with a semi-closed water circulation system. Feeding is done twice a day at satiation. The results showed that the ratio of different lipid sources had an effect on the total length growth of kelabau fry (P<0.05) but had no effect on the survival rate, absolute weight growth, or specific growth rate of kelabau fry (P > 0.05). Fish consuming diet C (50% fish oil and 50% corn oil) had the longest growth. Fish that consumed diet C also had relatively better survival rates and specific growth rates compared to groups of fish that consumed other feeds.